Negative pole piece, preparation method thereof, secondary battery and electric device

CN119213583APending Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280096192.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Secondary batteries are prone to expansion during long-term cycling and storage, leading to electrolyte bridge breakage, increased polarization, rate performance attenuation and shortened service life. In addition, existing technologies usually affect energy density and increase additives when reducing expansion force. Dosage affects safety performance.

Method used

Add an additive with a cavity structure to the negative electrode piece, and adjust the shell wall thickness and cavity volume ratio of the additive to meet 20nm≤d≤300nm and 40%≤Vh/Vw≤90% to slow down the expansion of the negative electrode. Negative effects, while optimizing the distribution of additives in the negative active material layer, improving structural stability and elastic deformation capability.

Benefits of technology

On the premise that the additive dosage is small, the expansion force of the secondary battery is effectively reduced, the safety performance is improved, and the cycle performance and rate performance are improved without affecting the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213583A_ABST
    Figure CN119213583A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece, a preparation method thereof, a secondary battery and an electric device, the negative pole piece comprises a negative current collector and a negative active material layer arranged on the negative current collector, the negative active material layer comprises a negative active material and an additive, the additive comprises a shell wall and a cavity located on the inner side of the shell wall, the thickness of the shell wall is recorded as d, the volume of the cavity is recorded as Vh, the volume of the additive is recorded as Vw, and the additive meets the conditions that d is larger than or equal to 20 nm and smaller than or equal to 300 nm, and Vh / Vw is larger than or equal to 40% and smaller than or equal to 90%. The expansion force of the secondary battery can be effectively reduced, and the safety performance of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Negative electrode sheet, preparation method thereof, secondary battery and electric device Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a negative electrode plate, a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the increasing application and promotion of secondary batteries, their safety issues have attracted increasing attention. If the safety of secondary batteries cannot be guaranteed, they will be unusable. Therefore, how to enhance the safety performance of secondary batteries is a technical problem that needs to be solved urgently.

[0003] Summary of the Invention

[0004] The purpose of the present application is to provide a negative electrode plate, a preparation method thereof, a secondary battery and an electrical device, which can effectively reduce the expansion force of the secondary battery and improve the safety performance of the secondary battery.

[0005] In a first aspect, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and an additive, the additive comprises a shell wall and a cavity located inside the shell wall, the thickness of the shell wall is denoted as d, and the volume of the cavity is denoted as V h , the volume of the additive is recorded as V w , and the additive satisfies 20nm≤d≤300nm and 40%≤V h / V w ≤90%.

[0006] When the additive satisfies both 20nm≤d≤300nm and 40%≤V h / V w When the additive's density is ≤90%, the additive's larger cavity structure allows for greater elastic deformation, effectively mitigating the negative effects of negative electrode expansion. Furthermore, the additive's structural stability prevents breakage or pulverization when subjected to significant elastic deformation. Therefore, this application effectively reduces the expansion force of secondary batteries and improves their safety while maintaining a low additive dosage and maintaining energy density.

[0007] In any embodiment of the present application, 25nm≤d≤200nm, optionally, 40nm≤d≤120nm. This is beneficial for improving the structural stability of the additive and balancing the strain capacity of the additive, thereby better mitigating the negative effects of negative electrode expansion. This allows the additive to be used in a small amount without affecting the energy density, effectively reducing the expansion force of the secondary battery and improving the safety performance of the secondary battery.

[0008] In any embodiment of the present application, 60%≤V h / V w ≤90%, optionally, 70%≤V h / V w ≤89%. This is conducive to the additive having a larger elastic deformation, providing a buffer space for the expansion of the negative electrode active material particles, thereby better mitigating the negative effects of negative electrode expansion, so that the additive can effectively reduce the expansion force of the secondary battery while using a small amount and without affecting the energy density, thereby improving the safety performance of the secondary battery.

[0009] In any embodiment of the present application, the thickness d of the shell wall of the additive, the volume V of the cavity of the additive h and the volume V of the additive w The test was performed as follows: a circular sample with a diameter of 0.5 cm was cut out from the negative electrode sheet, a TEM image of the cross section was obtained by transmission electron microscopy, the thickness of the shell wall of the additive and the volume particle size of the additive in the region were counted, and the cumulative distribution curves of the thickness of the shell wall of the additive and the volume particle size of the additive were obtained respectively. The thickness corresponding to the 50% percentage on the cumulative distribution curve was taken as the thickness d of the shell wall of the additive, and the volume particle size corresponding to the 50% percentage on the cumulative distribution curve was taken as the volume particle size Dv50 of the additive. According to the calculation formula of an ideal sphere, and with the volume particle size Dv50 obtained above as the diameter, the volume V of the additive was calculated. w , V w =(4 / 3)×π×(Dv50 / 2) 3 , the volume V of the cavity of the additive h =(4 / 3)×π×(Dv50 / 2-d) 3 .

[0010] In any embodiment of the present application, the additive includes one or more selected from hollow spheres and hollow polyhedrons, and may optionally include hollow spheres.

[0011] In any embodiment of the present application, the volume particle size Dv50 of the additive is 0.85 μm - 5 μm, and can be optionally 1 μm - 2.5 μm. Thus, on the one hand, it can effectively reduce the swelling force of the secondary battery and improve the safety performance, and on the other hand, it can ensure that the secondary battery has good cycle performance and rate performance.

[0012] In any embodiment of the present application, the volume particle size of the additive satisfies 0.5 ≤ (Dv90 - Dv10) / Dv50 ≤ 8, and optionally, 2 ≤ (Dv90 - Dv10) / Dv50 ≤ 5.

[0013] In any embodiment of the present application, the additive includes hollow carbon spheres, and can be optionally one or more selected from amorphous hollow carbon spheres, graphitized hollow carbon spheres, and hollow graphene spheres. Thus, it can better mitigate the negative effects caused by the swelling of the negative electrode, and effectively reduce the swelling force of the secondary battery and improve the safety performance of the secondary battery on the premise of using a small amount of the additive without affecting the energy density.

[0014] In any embodiment of the present application, based on the total weight of the negative electrode active material layer, the weight percentage content of the additive is 0.01 wt% - 3 wt%, and can be optionally 0.1 wt% - 2 wt%. The present application can effectively reduce the swelling force of the secondary battery and improve the safety performance of the secondary battery on the premise of using a small amount of the additive without affecting the energy density.

[0015] In any embodiment of the present application, along the width direction of the negative electrode active material layer, the negative electrode active material layer includes a first part and a second part located on the edge sides and a third part located between the first part and the second part. Taking the total width of the negative electrode active material layer as W, the width of the first part is 1 / 5W, the width of the second part is 1 / 5W, the width of the third part is 3 / 5W, the weight percentage content of the additive in the first part is w1, the weight percentage content of the additive in the second part is w2, the weight percentage content of the additive in the third part is w3, and 0 ≤ w1 / w3 < ½, 0 ≤ w2 / w3 < ½. By further adjusting the distribution of the additive in the width direction of the negative electrode active material layer, a high content of the additive is used in the third part, and a low content of the additive is used in the first part and the second part. Thus, not only can the swelling force of the secondary battery be effectively reduced and the safety performance of the secondary battery be improved, but also on the premise of achieving the same improvement effect of the swelling force, the amount of the additive can be further reduced and the energy density of the secondary battery can be increased.

[0016] In any embodiment of the present application, 0 < w1 / w3 ≤ 0.7, and optionally, 0 < w1 / w3 ≤ 0.5.

[0017] In any embodiment of the present application, 0 < w2 / w3 ≤ 0.7, optionally, 0 < w2 / w3 ≤ 0.5.

[0018] By further adjusting the ratio of the amount of additives in the first part and / or the second part to the amount of additives in the third part within the above range, it is possible to effectively reduce the swelling force of the secondary battery and improve the safety performance of the secondary battery on the premise of further reducing the amount of additives.

[0019] In any embodiment of the present application, 0 wt% ≤ w1 ≤ 2 wt%, optionally, 0 wt% < w1 ≤ 1 wt%.

[0020] In any embodiment of the present application, 0 wt% ≤ w2 ≤ 2 wt%, optionally, 0 wt% < w2 ≤ 1 wt%.

[0021] In any embodiment of the present application, 0.01 wt% ≤ w3 ≤ 5 wt%, optionally, 0.01 wt% ≤ w3 ≤ 2 wt%.

[0022] In any embodiment of the present application, w1 = w2.

[0023] In any embodiment of the present application, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode active material is 95 wt% - 99 wt%. This is beneficial to improving the energy density of the secondary battery.

[0024] In any embodiment of the present application, the negative electrode active material layer further includes a negative electrode binder and / or a negative electrode dispersant.

[0025] In any embodiment of the present application, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode binder is 1 wt% - 2.5 wt%.

[0026] In any embodiment of the present application, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode dispersant is 0.5 wt% - 1.5 wt%.

[0027] In any embodiment of the present application, the negative electrode active material layer further includes a negative electrode conductive agent. Optionally, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode conductive agent is 0 wt% - 1.5 wt%.

[0028] The second aspect of the present application provides a method for preparing a negative electrode plate, comprising the steps of: providing a negative electrode slurry comprising a negative electrode active material and an additive; coating the negative electrode slurry on a negative electrode current collector, and obtaining a negative electrode plate after drying and cold pressing, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material and an additive, the additive comprising a shell wall and a cavity located inside the shell wall, the thickness of the shell wall being denoted as d, and the volume of the cavity being denoted as V h , the volume of the additive is recorded as V w , and the additive satisfies 20nm≤d≤300nm and 40%≤V h / V w ≤90%.

[0029] In any embodiment of the present application, along the width direction of the negative electrode current collector, the negative electrode current collector includes a first region and a second region located on the edge side and a third region located between the first region and the second region. Taking the total width of the coated area of ​​the negative electrode current collector as W, the width of the first region is 1 / 5W, the width of the second region is 1 / 5W, and the width of the third region is 3 / 5W. In the method for preparing the negative electrode sheet, the negative electrode slurry is formulated to include a first slurry, a second slurry and a third slurry, and then the first slurry, the second slurry and the third slurry are respectively coated on the first region, the second region and the third region of the negative electrode current collector, and after drying, the first part, the second part and the third part of the negative electrode active material layer are respectively formed, wherein the weight percentage of the additive in the first part is w1, the weight percentage of the additive in the second part is w2, and the weight percentage of the additive in the third part is w3, and 0≤w1 / w3<1, 0≤w2 / w3<1.

[0030] In any embodiment of the present application, the first slurry, the second slurry and the third slurry are coated simultaneously in one process or in multiple steps.

[0031] A third aspect of the present application provides a secondary battery, comprising the negative electrode plate described in the first aspect of the present application, or the negative electrode plate prepared by the preparation method of the second aspect of the present application.

[0032] In any embodiment of the present application, the secondary battery satisfies 100≤K≤30000, optionally, 120≤K≤8000,

[0033]

[0034] λ is the porosity of the negative electrode sheet; ε is the thickness rebound rate of the third portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery; C0 is the initial capacity of the secondary battery, in mAh; d is the thickness of the shell wall of the additive, in nm; V h is the volume of the cavity of the additive, in nm 3 ; S is the area of ​​the single-layer negative electrode sheet, in mm 2 ; H is the initial thickness of the third portion of the negative electrode active material layer, in μm.

[0035] In any embodiment of the present application, 20%≤λ≤50%, optionally, 23%≤λ≤35%.

[0036] In any embodiment of the present application, 20%≤ε≤40%, optionally, 25%≤ε≤35%.

[0037] In any embodiment of the present application, 20 nm≤d≤300 nm, optionally, 40 nm≤d≤120 nm.

[0038] In any embodiment of the present application, 1×10 7 nm 3 ≤V h ≤1×10 12 nm 3 , optionally, 2.5×10 8 nm 3 ≤V h ≤1×10 10 nm 3 .

[0039] In any embodiment of the present application, 1×10 2 mm 2 ≤S≤1×10 8 mm 2 , optionally, 1×10 3 mm 2 ≤S≤1×10 6 mm 2 .

[0040] In any embodiment of the present application, 10 μm≤H≤250 μm, optionally, 40 μm≤H≤120 μm.

[0041] In any embodiment of the present application, when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, the thickness rebound rate of the first part of the negative electrode active material layer is recorded as ε1, the initial thickness of the first part of the negative electrode active material layer is recorded as H1, and the unit is μm. The thickness rebound rate of the second part of the negative electrode active material layer is recorded as ε2, the initial thickness of the second part of the negative electrode active material layer is recorded as H2, and the unit is μm. The secondary battery satisfies 0 <K1 / K≤1,0<K2 / K≤1,

[0042]

[0043]

[0044] In any embodiment of the present application, 0 <K1 / K≤0.95。

[0045] In any embodiment of the present application, 0 <K2 / K≤0.95。

[0046] In any embodiment of the present application, 100≤K1≤30000, optionally, 120≤K1≤8000.

[0047] In any embodiment of the present application, 100≤K2≤30000, optionally, 120≤K2≤8000.

[0048] In any embodiment of the present application, 15%≤ε1≤35%, optionally, 25%≤ε1≤31%.

[0049] In any embodiment of the present application, 15%≤ε2≤35%, optionally, 25%≤ε2≤31%.

[0050] In any embodiment of the present application, 10 μm≤H1≤250 μm, optionally, 40 μm≤H1≤120 μm.

[0051] In any embodiment of the present application, 10 μm ≤ H2 ≤ 250 μm, optionally, 40 μm ≤ H2 ≤ 120 μm.

[0052] A fourth aspect of the present application provides an electrical device comprising the secondary battery according to the third aspect of the present application.

[0053] The present application can effectively reduce the expansion force of the secondary battery and improve the safety performance of the secondary battery while using a small amount of additives and without affecting the energy density. The electrical device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0055] FIG1 is a schematic diagram of an embodiment of a negative electrode sheet of the present application.

[0056] FIG. 2 is a schematic diagram of an embodiment of a secondary battery of the present application.

[0057] FIG3 is an exploded schematic diagram of an embodiment of a secondary battery of the present application.

[0058] FIG4 is a schematic diagram of an embodiment of a battery module of the present application.

[0059] FIG5 is a schematic diagram of an embodiment of a battery pack of the present application.

[0060] FIG. 6 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 5 .

[0061] FIG. 7 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source.

[0062] FIG8 is a schematic diagram of a secondary battery expansion force test.

[0063] In the accompanying drawings, the drawings are not necessarily drawn to scale.

[0064] The accompanying drawings are explained as follows: 1 battery pack, 2 upper case, 3 lower case, 4 battery module, 5 secondary battery, 51 shell, 52 electrode assembly, 53 cover plate, 10 negative electrode sheet, 101 negative electrode current collector, 1011 first region, 1012 second region, 1013 third region, 102 negative electrode active material layer, 1021 first part, 1022 second part, 1023 third part, 201 sensor, 301 steel plate, 302 steel plate, 303 steel plate. DETAILED DESCRIPTION

[0065] Below, the embodiments of the negative electrode sheet, its preparation method, secondary battery and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0066] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0067] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0068] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0069] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0070] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0071] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0072] Unless otherwise specified, in this application, the terms "first", "second", "third", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.

[0073] In this application, the terms "plurality" and "multiple" refer to two or more.

[0074] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.

[0075] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0076] In the development of secondary battery technology, in addition to improving the electrochemical performance of secondary batteries, safety performance is also an issue that cannot be ignored. During the long-term circulation and storage of secondary batteries, secondary batteries are prone to swelling due to factors such as changes in the lattice structure of the active materials. As the number of cycles and storage periods of the secondary batteries increases, the expansion force of the secondary batteries gradually increases. When the expansion force of the secondary battery is too high, the electrolyte infiltrated in the electrode will be squeezed out, which can easily lead to electrolyte bridge breakage. At this time, the active ion transmission channel inside the secondary battery is blocked, the polarization of the secondary battery increases significantly, the rate performance decays rapidly, the capacity retention rate decreases significantly, and the service life is greatly shortened. In addition, when the expansion force of the secondary battery is too high, the structure of the secondary battery pack is prone to failure, posing a safety risk.

[0077] Therefore, effective technical means are needed to reduce the expansion force of secondary batteries and improve the safety performance of secondary batteries.

[0078] During the long-term cycling and storage of secondary batteries, the thickness of the negative electrode changes more significantly than that of the positive electrode, and current research suggests that the increase in the thickness of the negative electrode is the main reason for the increase in the expansion force of the secondary battery. Prior art attempts to prepare negative electrode sheets by adding hollow carbon spheres and mixing them with negative electrode active materials during the preparation of secondary batteries. The hollow carbon spheres mitigate the negative effects of the change in the thickness of the negative electrode, thereby improving the cycle performance of the secondary battery and reducing the irreversible capacity loss. However, the inventors of this application discovered during their research that, in order to effectively reduce the expansion force of the secondary battery, the prior art generally uses a high amount of hollow carbon spheres, which significantly reduces the energy density of the secondary battery.

[0079] In view of this, the inventors of the present application discovered during an in-depth study of the problem of secondary battery expansion that by adding an additive with a cavity structure to the negative electrode plate and adjusting the shell wall thickness and cavity volume ratio of the additive, the expansion force of the secondary battery can be effectively reduced and the safety performance of the secondary battery can be improved while using a small amount of additive and not affecting the energy density.

[0080] Specifically, a first aspect of an embodiment of the present application provides a negative electrode plate.

[0081] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and an additive. The additive includes a shell wall and a cavity located inside the shell wall. The thickness of the shell wall is denoted as d, and the volume of the cavity is denoted as V. h , the volume of the additive is recorded as V w , and the additive satisfies 20nm≤d≤300nm and 40%≤V h / V w ≤90%.

[0082] The additive used in the negative electrode plate of the present application has a hollow structure. The cavity structure can provide a buffer space to buffer the expansion of the negative electrode, thereby reducing the expansion force of the secondary battery. The inventors of the present application found in the process of in-depth research on the expansion problem of secondary batteries that when the thickness d of the shell wall of the additive is too small and / or the volume of the cavity of the additive accounts for V h / V w When the thickness d of the shell wall of the additive is too large and / or the volume of the cavity of the additive accounts for V h / V w When the additive is too small, the shell wall structure of the additive is more stable, but the additive is not easy to deform elastically, which leads to poor buffering effect on the expansion of the negative electrode, and thus cannot effectively reduce the expansion force of the secondary battery and improve the safety performance of the secondary battery. When the additive satisfies both 20nm≤d≤300nm and 40%≤V h / V w When the additive's density is ≤90%, the additive's larger cavity structure allows for greater elastic deformation, effectively mitigating the negative effects of negative electrode expansion. Furthermore, the additive's structural stability prevents breakage or pulverization when subjected to significant elastic deformation. Therefore, this application effectively reduces the expansion force of secondary batteries and improves their safety while maintaining a low additive dosage and maintaining energy density.

[0083] In the present application, the thickness d of the shell wall of the additive, the volume V of the cavity of the additive h and the volume V of the additive w The test can be obtained by the following method: a circular sample with a diameter of 0.5 cm is cut out from the negative electrode sheet, and a TEM image of the cross section is obtained by a transmission electron microscope (TEM), and the thickness of the shell wall of the additive and the volume particle size of the additive in the region are counted, and the cumulative distribution curves of the thickness of the shell wall of the additive and the volume particle size of the additive are obtained respectively, and the thickness corresponding to the 50% percentage on the cumulative distribution curve is taken as the thickness d of the shell wall of the additive, and the volume particle size corresponding to the 50% percentage on the cumulative distribution curve is taken as the volume particle size Dv50 of the additive; according to the calculation formula of the ideal sphere, and with the volume particle size Dv50 obtained above as the diameter, the volume V of the additive is calculated. w , V w =(4 / 3)×π×(Dv50 / 2) 3 , the volume V of the cavity of the additive h =(4 / 3)×π×(Dv50 / 2-d) 3 .

[0084] In the present application, the thickness d of the shell wall satisfies 20nm≤d≤300nm. For example, d can be 25nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 300nm or a range consisting of any of the above values.

[0085] In some embodiments, optionally, 25nm≤d≤200nm, 25nm≤d≤180nm, 25nm≤d≤150nm, 30nm≤d≤150nm, 40nm≤d≤120nm, and 40nm≤d≤100nm. This helps improve the structural stability of the additive and balance the strain capacity of the additive, thereby better mitigating the negative effects of negative electrode expansion. This allows the additive to effectively reduce the expansion force of the secondary battery while maintaining a small dosage and without affecting the energy density, thereby improving the safety performance of the secondary battery.

[0086] In this application, the volume of the cavity of the additive accounts for V h / V w Satisfy 40%≤V h / V w ≤90%, for example, V h / Vw It can be 48%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or any range consisting of the above values.

[0087] In some embodiments, optionally, 50% ≤ V h / V w ≤90%, 55%≤V h / V w ≤90%, 60%≤V h / V w ≤90%, 65%≤V h / V w ≤90%, 70%≤V h / V w ≤90%, 70%≤V h / V w ≤89%. This is conducive to the additive having a larger elastic deformation, providing a buffer space for the expansion of the negative electrode active material particles, thereby better mitigating the negative effects of negative electrode expansion, so that the additive can effectively reduce the expansion force of the secondary battery while using a small amount and without affecting the energy density, thereby improving the safety performance of the secondary battery.

[0088] In some embodiments, 25 nm ≤ d ≤ 200 nm and 60% ≤ V h / V w ≤90%. Optionally, 40nm≤d≤120nm and 70%≤V h / V w ≤89%. This helps the additive to better combine greater elastic deformation with higher structural stability, thereby better mitigating the negative effects of negative electrode expansion, effectively reducing the expansion force of the secondary battery while using a smaller amount of the additive and without affecting the energy density, thereby improving the safety performance of the secondary battery.

[0089] In some embodiments, the additive includes one or more selected from hollow spheres and hollow polyhedrons. In this application, the term "hollow sphere" refers to a structure having a sphere or a structure close to a sphere, and not all spheres are controlled to be ideal spheres; "hollow polyhedron" can include both regular polyhedrons, such as cubes, and irregular polyhedrons.

[0090] In some embodiments, the additive comprises hollow spheres, which can better mitigate the negative effects of negative electrode expansion, effectively reducing the expansion force of the secondary battery while using a small amount of the additive and without affecting the energy density, thereby improving the safety performance of the secondary battery.

[0091] In some embodiments, for example, the additive includes hollow carbon spheres, which may be one or more selected from amorphous hollow carbon spheres, graphitized hollow carbon spheres, and hollow graphene spheres. This can effectively mitigate the negative effects of negative electrode expansion, effectively reducing the expansion force of the secondary battery while maintaining a relatively small additive dosage and without compromising energy density, thereby improving the safety of the secondary battery.

[0092] Further research by the inventors revealed that the particle size of the additive affects the safety performance of the secondary battery. Smaller additive particles less effectively mitigate the negative effects of negative electrode expansion, resulting in a poorer reduction in the secondary battery's expansion force. Furthermore, smaller additive particles more easily fill the gaps between the negative electrode active material particles, resulting in a higher compaction density and lower porosity in the negative electrode sheet. When the compaction density of the negative electrode sheet is high, the thickness rebound of the negative electrode sheet during use of the secondary battery is more significant, which can easily lead to a significant increase in the expansion force of the secondary battery, which is not conducive to improving the safety performance of the secondary battery. When the compaction density of the negative electrode sheet is high, the negative electrode sheet has poor wettability and liquid retention by the electrolyte. Therefore, when the expansion force of the secondary battery increases, the electrolyte in the negative electrode sheet is more easily squeezed out, which in turn makes it more likely to cause electrolyte bridge breakage, negative electrode lithium deposition, and secondary battery cycle drop. When the compaction density of the negative electrode sheet is high, the ion conductivity characteristics of the negative electrode sheet deteriorate, which is not conducive to the cycle performance and rate performance of the secondary battery. At the same time, the inventors found in further research that the particle size of the additive should not be too large. When the additive dosage is the same, the larger the particle size of the additive, the more uneven its distribution in the negative electrode active material layer, which leads to a weaker effect on mitigating the negative effects of negative electrode expansion, a poorer effect on reducing the expansion force of the secondary battery, and a poorer effect on improving the safety performance of the secondary battery. In some embodiments, the volume particle size Dv50 of the additive may be 0.85 μm-5 μm, optionally 0.85 μm-4 μm, 0.9 μm-3 μm, 1 μm-2.5 μm, or 1 μm-2 μm. This can effectively reduce the expansion force of the secondary battery and improve its safety, while also ensuring good cycle performance and rate capability.

[0093] In some embodiments, the volume particle size of the additive satisfies 0.5≤(Dv90-Dv10) / Dv50≤8, optionally, 1≤(Dv90-Dv10) / Dv50≤5, 2≤(Dv90-Dv10) / Dv50≤5.

[0094] In this application, the volume particle sizes Dv10, Dv50, and Dv90 of a material are generally known in the art and represent the particle sizes corresponding to the 10%, 50%, and 90% cumulative volume distribution percentages, respectively. These can be measured using instruments and methods known in the art. For example, these can be measured using a laser particle size analyzer in accordance with GB / T 19077-2016. A Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK, can be used as the testing instrument.

[0095] In some embodiments, the weight percentage of the additive, based on the total weight of the negative electrode active material layer, is 0.01wt%-3wt%, optionally 0.1wt%-2.5wt%, 0.1wt%-2wt%, 0.1wt%-1.5wt%, or 0.1wt%-1wt%. This application can effectively reduce the expansion force of the secondary battery and improve the safety performance of the secondary battery while using a small amount of additive and without affecting the energy density.

[0096] Currently, in existing negative electrode plates, hollow microspheres are uniformly distributed. While this reduces the expansion force of the secondary battery, it also reduces the proportion of negative electrode active material, thereby reducing the energy density of the secondary battery. During their in-depth research on the expansion of secondary batteries, the inventors of this application discovered that the expansion force of secondary batteries is not uniformly distributed. Through in-depth research on the distribution characteristics of the expansion force of secondary batteries, the inventors achieved an effective reduction in the expansion force of secondary batteries while further reducing the amount of additives used, thereby improving the safety performance of the secondary battery.

[0097] FIG1 is a schematic diagram of one embodiment of a negative electrode plate 10 of the present application. As shown in FIG1 , the negative electrode plate 10 includes a negative electrode current collector 101 and a negative electrode active material layer 102 disposed on the negative electrode current collector 101. Along the width direction of the negative electrode active material layer 102, the negative electrode active material layer 102 includes a first portion 1021, a second portion 1022 located at an edge thereof, and a third portion 1023 located between the first portion 1021 and the second portion 1022. Based on the total width W of the negative electrode active material layer 102, the width of the first portion 1021 is 1 / 5 W, the width of the second portion 1022 is 1 / 5 W, and the width of the third portion 1023 is 3 / 5 W. The weight percentage of the additive in the first portion 1021 is w1, the weight percentage of the additive in the second portion 1022 is w2, and the weight percentage of the additive in the third portion 1023 is w3, and 0≤w1 / w3<1 and 0≤w2 / w3<1.

[0098] During an in-depth study of the distribution of the expansion force of secondary batteries, the inventors discovered that during the long-term circulation and storage of secondary batteries, the large surface of the electrode assembly is subjected to the highest degree of compression. Therefore, by further adjusting the distribution of additives in the width direction of the negative electrode active material layer, a high content of additives is used in the third part, and a low content of additives is used in the first and second parts. This not only effectively reduces the expansion force of the secondary battery and improves the safety performance of the secondary battery, but also further reduces the amount of additives used while achieving the same expansion force improvement effect, thereby increasing the energy density of the secondary battery.

[0099] In some embodiments, 0 <w1 / w3≤0.8,0<w1 / w3≤0.7,0<w1 / w3≤0.6,0<w1 / w3≤0.5,0<w1 / w3≤0.4。

[0100] In some embodiments, 0 <w2 / w3≤0.8,0<w2 / w3≤0.7,0<w2 / w3≤0.6,0<w2 / w3≤0.5,0<w2 / w3≤0.4。

[0101] By further adjusting the ratio of the amount of the additive in the first part and / or the second part to the amount of the additive in the third part within the above range, the expansion force of the secondary battery can be effectively reduced while further reducing the amount of the additive, and the safety performance of the secondary battery can be improved.

[0102] In some embodiments, 0wt%≤w1≤2wt%, optionally, 0wt% <w1≤1.8wt%,0wt%<w1≤1.6wt%,0wt%<w1≤1.4wt%,0wt%<w1≤1.2wt%,0wt%<w1≤1wt%,0wt%<w1≤0.8wt%,0wt%<w1≤0.6wt%,0wt%<w1≤0.4wt%。

[0103] In some embodiments, 0wt%≤w2≤2wt%, optionally, 0wt% <w2≤1.8wt%,0wt%<w2≤1.6wt%,0wt%<w2≤1.4wt%,0wt%<w2≤1.2wt%,0wt%<w2≤1wt%,0wt%<w2≤0.8wt%,0wt%<w2≤0.6wt%,0wt%<w2≤0.4wt%。

[0104] In some embodiments, 0.01wt%≤w3≤5wt%, optionally, 0.01wt%≤w3≤4.5wt%, 0.01wt%≤w3≤4wt%, 0.01wt%≤w3≤3.5wt%, 0.01wt%≤w3≤3wt%, 0.01wt%≤w3≤2.5wt%, 0.01wt%≤w3≤2wt%, 0.01wt%≤w3≤1.5wt%, 0.01wt%≤w3≤1wt%.

[0105] In some embodiments, w1=w2.

[0106] In the present application, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer may be provided on either or both of the two facing surfaces of the negative electrode current collector.

[0107] In some embodiments, the negative electrode active material may be a negative electrode active material for a secondary battery that is well known in the art. As an example, the negative electrode active material includes, but is not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide, and tin alloy material. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials for secondary batteries may also be used.

[0108] In some embodiments, the volume particle size Dv50 of the negative electrode active material is 8 μm-22 μm, and can be optionally 12 μm-18 μm.

[0109] In some embodiments, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode active material may be 95 wt % to 99 wt %, thereby facilitating improvement of the energy density of the secondary battery.

[0110] In some embodiments, the negative electrode active material layer further includes a negative electrode binder and / or a negative electrode dispersant. The negative electrode binder is used to improve the adhesion between the negative electrode active material particles and between the negative electrode active material and the negative electrode current collector, so that the negative electrode sheet forms a good electronic network. The present application does not particularly limit the type of negative electrode binder, and materials known in the art can be used. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode binder may be greater than 0 and less than or equal to 2.5wt%, and may be optionally 1wt%-2.5wt%. The negative electrode dispersant is used to improve the stability and dispersibility of the negative electrode slurry. The present application does not particularly limit the type of negative electrode dispersant, and materials known in the art can be used. As an example, the negative electrode dispersant may include sodium carboxymethyl cellulose (CMC). In some embodiments, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode dispersant may be greater than 0 and less than or equal to 1.5 wt %, and may be 0.5 wt % to 1.5 wt %.

[0111] In some embodiments, the negative electrode active material layer further includes a negative electrode conductive agent. The present application does not particularly limit the type of negative electrode conductive agent, and materials known in the art can be used. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, graphene, and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode active material layer, the weight percentage of the negative electrode conductive agent may be 0wt%-1.5wt%. When the weight percentage of the negative electrode conductive agent is 0wt%, it means that no negative electrode conductive agent is added.

[0112] In some embodiments, the negative electrode active material layer may optionally further include other additives, such as PTC thermistor materials.

[0113] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0114] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein may further include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate described herein may further include a protective layer covering the surface of the negative electrode active material layer.

[0115] Preparation method

[0116] A second aspect of the embodiments of the present application provides a method for preparing a negative electrode sheet.

[0117] The method for preparing the negative electrode plate comprises the following steps: providing a negative electrode slurry comprising a negative electrode active material and an additive; coating the negative electrode slurry on a negative electrode current collector, drying, and cold pressing to obtain a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material and an additive, the additive comprises a shell wall and a cavity located inside the shell wall, the thickness of the shell wall is denoted as d, and the volume of the cavity is denoted as V h , the volume of the additive is recorded as V w , and the additive satisfies 20nm≤d≤300nm and 40%≤V h / V w ≤90%.

[0118] In some embodiments, as shown in FIG1 , along the width direction of the negative electrode current collector 101, the negative electrode current collector 101 includes a first region 1011 and a second region 1012 located on the edge side and a third region 1013 located between the first region 1011 and the second region 1012. Taking the total width of the coating area of ​​the negative electrode current collector 101 as W, the width of the first region 1021 is 1 / 5W, the width of the second region 1022 is 1 / 5W, and the width of the third region 1023 is 3 / 5W. In the preparation method of the negative electrode sheet, the negative electrode slurry is prepared to include the first slurry, the second slurry and the third slurry. The first slurry, the second slurry, and the third slurry are then applied to the first region 1011, the second region 1012, and the third region 1013 of the negative electrode current collector, respectively. After drying, they form the first portion 1021, the second portion 1022, and the third portion 1023 of the negative electrode active material layer, respectively. The weight percentage of the additive in the first portion 1021 is w1, the weight percentage of the additive in the second portion 1022 is w2, and the weight percentage of the additive in the third portion 1023 is w3, and 0 ≤ w1 / w3 < 1, and 0 ≤ w2 / w3 < 1. In this application, the total width of the coated region of the negative electrode current collector is the same as the total width of the negative electrode active material layer.

[0119] In some embodiments, the negative electrode slurry includes a negative electrode binder and / or a negative electrode dispersant.

[0120] In some embodiments, the negative electrode slurry may include a negative electrode conductive agent. Of course, the negative electrode slurry may also not include a negative electrode conductive agent.

[0121] In some embodiments, the solvent for preparing the negative electrode slurry may be N-methylpyrrolidone (NMP) or deionized water, but the present application is not limited thereto.

[0122] The present application has no particular restrictions on the concentration, coating weight, coating thickness and other parameters of the negative electrode slurry, which can be selected according to needs.

[0123] During the preparation of the negative electrode slurry, the form and timing of the additives are not particularly limited. For example, the additives can be added in the form of a solid powder or a suspension; the additives can be added during the stirring process of the negative electrode slurry or during the dry mixing stage.

[0124] During the coating process of the negative electrode slurry, the first slurry, the second slurry and the third slurry may be coated simultaneously in one process or in multiple steps.

[0125] The preparation method provided in the second aspect of the present application can prepare the negative electrode sheet of any embodiment of the first aspect of the present application. In the preparation process of the negative electrode sheet, the specific types and amounts of some raw materials used can be referred to the negative electrode sheet of the first aspect of the present application, and will not be repeated here.

[0126] In addition, it should be understood that although the first region 1011, the second region 1012 and the third region 1013 of the negative electrode current collector 101 are distinguished by lines in Figure 1, and the first part 1021, the second part 1022 and the third part 1023 of the negative electrode active material layer 102 are distinguished, in fact, there may be no interface, and the negative electrode current collector 101 as a whole can be continuous, and the negative electrode active material layer 102 as a whole can also be continuous.

[0127] In some embodiments, along the width direction of the negative electrode current collector 101, the negative electrode current collector 101 may also include an uncoated area (not shown) where the negative electrode active material layer 102 is not provided, that is, the total width of the negative electrode current collector 101 is greater than the total width of the coated area of ​​the negative electrode current collector 101 (or the total width of the negative electrode active material layer).

[0128] secondary batteries

[0129] A third aspect of the present application provides a secondary battery. A secondary battery generally includes a positive electrode, a negative electrode, and an electrolyte. The present application does not specifically limit the type of secondary battery; for example, the secondary battery may be a lithium-ion battery, a sodium-ion battery, or the like.

[0130] The negative electrode plate used in the secondary battery of the present application includes the negative electrode plate described in any embodiment of the first aspect of the implementation of the present application or the negative electrode plate prepared by the preparation method described in any embodiment of the second aspect of the implementation of the present application.

[0131] In some embodiments, the secondary battery satisfies 100≤K≤30000,

[0132]

[0133] λ is the porosity of the negative electrode sheet; ε is the thickness rebound rate of the third portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery; C0 is the initial capacity of the secondary battery, in mAh; d is the thickness of the shell wall of the additive, in nm; V h is the volume of the cavity of the additive, in nm 3 ; S is the area of ​​the single-layer negative electrode sheet, in mm 2 ; H is the initial thickness of the third portion of the negative electrode active material layer, in μm.

[0134] The inventors have found through in-depth research that when the above parameter K of the secondary battery satisfies a value between 100 and 30,000, the secondary battery can have smaller expansion force and higher safety performance, and the secondary battery can also have higher energy density.

[0135] In some embodiments, optionally, 100≤K≤20000, 120≤K≤16000, 120≤K≤12000, 120≤K≤10000, 120≤K≤9000, 120≤K≤8000, 200≤K≤8000, 300≤K≤8000, 400≤K≤8000, 500≤K≤8000.

[0136] In this application, the porosity of the negative electrode sheet has a well-known meaning in the art and can be measured using methods known in the art. An exemplary test method is as follows: take a negative electrode sheet that has been coated on one side and cold-pressed (if it is a negative electrode sheet coated on both sides, the negative electrode active material layer on one side can be wiped off first), punch it into small disc samples of a certain area, and calculate the apparent volume V1 of the negative electrode sheet; refer to GB / T24586-2009, use an inert gas (such as helium or nitrogen) as a medium, adopt a gas replacement method, and use a true density tester to measure the true volume V2 of the negative electrode sheet. Porosity of the negative electrode sheet = (V1-V2) / V1×100%. Multiple negative electrode sheet samples with good appearance and no powder falling off the edges (such as 30 pieces) can be taken for testing, and the results are averaged, thereby improving the accuracy of the test results. The testing instrument can be a Micromeritics AccuPyc II 1340 true density tester.

[0137] ε is the thickness rebound rate of the third portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, ε = (H′ - H) / H. H′ is the thickness of the third portion of the negative electrode active material layer measured when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery. H is the initial thickness of the third portion of the negative electrode active material layer. In this application, it is the thickness of the third portion of the negative electrode active material layer measured when the number of cycles of the secondary battery is less than or equal to 50.

[0138] In the present application, the initial capacity C0 of a secondary battery refers to the capacity of the secondary battery with a cycle number of 50 or less.

[0139] In this application, S is the area of ​​a single-layer negative electrode sheet. When the electrode assembly has a laminated structure, S = the width of the negative electrode sheet × the length of the negative electrode sheet; when the electrode assembly has a wound structure, S = half the circumference of the winding needle × the width of the negative electrode sheet.

[0140] In some embodiments, 20%≤λ≤50%. For example, λ can be 21%, 23%, 25%, 27%, 29%, 31%, 33%, 35%, 37%, 39%, 41%, 43%, 45%, 50%, or any range thereof. Alternatively, 23%≤λ≤35%.

[0141] In some embodiments, 20%≤ε≤40%, for example, ε can be 21%, 23%, 25%, 27%, 29%, 31%, 33%, 35%, 37%, 40% or any range thereof. Alternatively, 25%≤ε≤35%.

[0142] In some embodiments, 20 nm ≤ d ≤ 300 nm, for example, d can be 25 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 300 nm, or any range thereof. Alternatively, 25 nm ≤ d ≤ 200 nm, 25 nm ≤ d ≤ 180 nm, 25 nm ≤ d ≤ 150 nm, 30 nm ≤ d ≤ 150 nm, 40 nm ≤ d ≤ 120 nm, or 40 nm ≤ d ≤ 100 nm.

[0143] In some embodiments, 1×10 7 nm 3 ≤V h ≤1×10 12 nm 3 , optionally, 5×10 7 nm 3 ≤V h ≤2×10 10 nm 3 , 1×10 8 nm 3 ≤V h ≤1×10 10 nm 3 , 2.5×10 8 nm 3 ≤V h ≤1×10 10 nm 3 .

[0144] In some embodiments, 1×10 2 mm 2 ≤S≤1×10 8 mm 2 , optionally, 1×10 3 mm 2 ≤S≤1×10 6 mm 2 , 1×104 mm 2 ≤S≤1×10 6 mm 2 。

[0145] In some embodiments, 10 μm ≤ H ≤ 250 μm. Optionally, 40 μm ≤ H ≤ 120 μm, 40 μm ≤ H ≤ 100 μm, 40 μm ≤ H ≤ 80 μm.

[0146] In some embodiments, when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, the thickness rebound rate of the first part of the negative electrode active material layer is denoted as ε1, the initial thickness of the first part of the negative electrode active material layer is denoted as H1, with the unit of μm, the thickness rebound rate of the second part of the negative electrode active material layer is denoted as ε2, the initial thickness of the second part of the negative electrode active material layer is denoted as H2, with the unit of μm, and the secondary battery satisfies 0 < K1 / K ≤ 1, 0 < K2 / K ≤ 1.

[0147]

[0148]

[0149] The inventors found in in - depth research that when the above parameters K1, K2 and K of the secondary battery satisfy 0 < K1 / K ≤ 1, 0 < K2 / K ≤ 1, the secondary battery can have a smaller swelling force and higher safety performance, and at the same time, the secondary battery can also have a higher energy density.

[0150] In some embodiments, 0 < K1 / K ≤ 0.95, 0 < K1 / K ≤ 0.94, 0 < K1 / K ≤ 0.92, 0 < K1 / K ≤ 0.90, 0 < K1 / K ≤ 0.88, 0 < K1 / K ≤ 0.86. This is beneficial to further improving the energy density of the secondary battery.

[0151] In some embodiments, 0 < K2 / K ≤ 0.95, 0 < K2 / K ≤ 0.94, 0 < K2 / K ≤ 0.92, 0 < K2 / K ≤ 0.90, 0 < K2 / K ≤ 0.88, 0 < K2 / K ≤ 0.86. This is beneficial to further improving the energy density of the secondary battery.

[0152] In some embodiments, 100≤K1≤30000, optionally, 100≤K1≤20000, 120≤K1≤16000, 120≤K1≤12000, 120≤K1≤10000, 120≤K1≤9000, 120≤K1≤8000, 200≤K1≤8000, 300≤K1≤8000, 400≤K1≤8000, and 500≤K1≤8000. The inventors have found through in-depth research that when the parameter K1 of the secondary battery is within the above range, the secondary battery can have a further improved energy density while having a smaller expansion force and higher safety performance.

[0153] In some embodiments, 100≤K2≤30000, optionally, 100≤K2≤20000, 120≤K2≤16000, 120≤K2≤12000, 120≤K2≤10000, 120≤K2≤9000, 120≤K2≤8000, 200≤K2≤8000, 300≤K2≤8000, 400≤K2≤8000, and 500≤K2≤8000. The inventors have found through in-depth research that when the secondary battery parameter K2 is within the above range, the secondary battery can have a further improved energy density while having a smaller expansion force and higher safety performance.

[0154] In some embodiments, 15%≤ε1≤35%, optionally, 25%≤ε1≤31%.

[0155] In some embodiments, 15%≤ε2≤35%, optionally, 25%≤ε2≤31%.

[0156] In some embodiments, 10 μm≤H1≤250 μm, optionally, 40 μm≤H1≤120 μm, 40 μm≤H1≤100 μm, 40 μm≤H1≤80 μm.

[0157] In some embodiments, 10 μm≤H2≤250 μm, optionally, 40 μm≤H2≤120 μm, 40 μm≤H2≤100 μm, 40 μm≤H2≤80 μm.

[0158] ε1 is the thickness rebound rate of the first portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, ε1 = (H1′-H1) / H1. H1′ is the thickness of the first portion of the negative electrode active material layer measured when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery. H1 is the initial thickness of the first portion of the negative electrode active material layer. In this application, it is the thickness of the first portion of the negative electrode active material layer measured when the number of cycles of the secondary battery is less than or equal to 50.

[0159] ε2 is the thickness rebound rate of the second portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, ε2 = (H2′-H2) / H2. H2′ is the thickness of the second portion of the negative electrode active material layer measured when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery. H2 is the initial thickness of the second portion of the negative electrode active material layer. In this application, it is the thickness of the second portion of the negative electrode active material layer measured when the number of cycles of the secondary battery is less than or equal to 50.

[0160] In some embodiments, H, H1, and H2 may be the same, that is, when the number of cycles of the secondary battery is less than or equal to 50, the thicknesses of the first portion, the second portion, and the third portion of the negative electrode active material are the same.

[0161] In this application, the thickness parameters of the negative electrode active material layer (such as H, H′, H1, H1′, H2, H2′) all refer to the thickness of the negative electrode active material layer located on a single side of the negative electrode current collector.

[0162] It should be noted that the parameters of each negative electrode active material layer given in this application (such as thickness, porosity, structure and content of additives, etc.) refer to the parameters of the negative electrode active material layer on a single side of the negative electrode current collector. When the negative electrode active material layer is provided on both sides of the negative electrode current collector, the parameters of the negative electrode active material layer on either side that meet the requirements of this application are considered to fall within the scope of protection of this application.

[0163] [Positive electrode]

[0164] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector has two surfaces that oppose each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.

[0165] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may be a positive electrode active material for a secondary battery known in the art.

[0166] When the secondary battery of the present application is a lithium ion battery, the positive electrode active material may include one or more of a lithium transition metal oxide, a lithium phosphate containing an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium phosphate containing an olivine structure may include one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for secondary batteries may also be used.

[0167] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion secondary battery may include a general formula of Li a Ni b Co c M d O e A f One or more lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes one or more selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes one or more selected from N, F, S and Cl.

[0168] As an example, the positive electrode active material for lithium ion secondary batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 and LiMnPO4.

[0169] When the secondary battery of the present application is a sodium ion battery, the positive electrode active material may include but is not limited to one or more of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.

[0170] As an example, the positive active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials and general formula X p M' q (PO4) r O x Y 3-x One or more materials. p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes H + 、Li + 、Na + , K + and NH4 + One or more of, M' is a transition metal cation, which can be selected from one or more of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, which can be selected from one or more of F, Cl and Br.

[0171] In the present application, the modified compounds of the above-mentioned positive electrode active materials may be the ones subjected to doping modification and / or surface coating modification on the positive electrode active materials.

[0172] In some embodiments, the positive electrode active material layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. For example, the positive electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0173] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode binder. This application does not particularly limit the type of the positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.

[0174] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0175] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0176] [Electrolytes]

[0177] The electrolyte conducts active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected based on needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (i.e., electrolyte solutions).

[0178] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0179] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0180] When the secondary battery of the present application is a sodium ion battery, the electrolyte salt may include sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP). One or more.

[0181] The type of the solvent is not particularly limited and can be selected according to demand. In some embodiments, for example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE). One or more.

[0182] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0183] [Isolation film]

[0184] Secondary batteries using electrolytes and some secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. This application does not have any special restrictions on the type of separator, and any well-known porous structure separator with good chemical stability and mechanical stability can be selected. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer are the same or different.

[0185] In some embodiments, the isolation membrane may include a base film and an optional protective coating. The base film may include a non-woven fabric, a film, or a composite film having a porous structure, and the material of the base film may include one or more of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, and polyimide.

[0186] The surface of the base film may or may not be provided with a protective coating. In some embodiments, at least one surface of the base film is provided with a protective coating, which may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic layer.

[0187] The inorganic layer includes inorganic particles and a binder, and the inorganic particles include but are not limited to one or more of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0188] The polymer layer comprises a polymer, and the material of the polymer includes but is not limited to one or more of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether and polyvinylidene fluoride.

[0189] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process.

[0190] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0191] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0192] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG2 shows a secondary battery 5 with a square structure as an example.

[0193] In some embodiments, as shown in FIG3 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0194] The preparation method of the secondary battery of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. The secondary battery is then vacuum packaged, allowed to stand, formed, and shaped.

[0195] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0196] Figure 4 is a schematic diagram of an exemplary battery module 4. As shown in Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.

[0197] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0198] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0199] Figures 5 and 6 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 5 and 6, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 may be arranged in any manner within the battery box.

[0200] Electrical devices

[0201] The present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0202] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0203] Figure 7 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0204] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.

[0205] Example

[0206] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.

[0207] Example 1-1

[0208] Preparation of positive electrode

[0209] 97 wt% of the positive electrode active material LiFePO4, 1 wt% of the conductive agent carbon black (Super P), and 2 wt% of the binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an appropriate amount of solvent NMP to form a uniform positive electrode slurry; the positive electrode slurry was evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, the positive electrode sheet was obtained.

[0210] Preparation of negative electrode sheet

[0211] 96.99wt% of negative electrode active material graphite, 1.8wt% of binder styrene-butadiene rubber (SBR), and 1.2wt% of dispersant sodium carboxymethyl cellulose (CMC) were thoroughly stirred and mixed in an appropriate amount of solvent deionized water, and then 0.01wt% of amorphous hollow carbon balls were added and stirred evenly to form a negative electrode slurry; the negative electrode slurry was evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained.

[0212] Preparation of electrolyte

[0213] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0214] Preparation of isolation membrane

[0215] A porous polyethylene film was used as the separator.

[0216] Preparation of secondary batteries

[0217] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping, capacity, and other processes, a secondary battery is obtained.

[0218] Examples 1-2 to 1-9

[0219] The preparation method of the secondary battery is similar to that of Example 1-1, except that the preparation parameters of the negative electrode sheet are different. The specific parameters are detailed in Table 1, and in the preparation of the negative electrode sheet, the addition amounts of the binder and dispersant remain unchanged.

[0220] Comparative Example 1-1

[0221] The preparation method of the secondary battery is similar to that of Example 1-1, except that the preparation parameters of the negative electrode are different.

[0222] 97.1wt% of negative electrode active material graphite, 1.8wt% of binder styrene-butadiene rubber (SBR), 0.7wt% of dispersant sodium carboxymethyl cellulose (CMC), and 0.4wt% of conductive agent carbon black (Super P) were thoroughly stirred and mixed in an appropriate amount of solvent deionized water to form a negative electrode slurry; the negative electrode slurry was coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained.

[0223] Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-2

[0224] The preparation method of the secondary battery is similar to that of Example 1-1, except that the preparation parameters of the negative electrode sheet are different. The specific parameters are detailed in Table 2, and in the preparation of the negative electrode sheet, the addition amounts of the binder and dispersant remain unchanged.

[0225] Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-2

[0226] The preparation method of the secondary battery is similar to that of Example 1-1, except that the preparation parameters of the negative electrode sheet are different. The specific parameters are detailed in Table 3, and in the preparation of the negative electrode sheet, the addition amounts of the binder and dispersant remain unchanged.

[0227] Examples 4-1 to 4-4

[0228] The preparation method of the secondary battery is similar to that of Example 1-1, except that the preparation parameters of the negative electrode sheet are different. The specific parameters are detailed in Table 4, and in the preparation of the negative electrode sheet, the addition amounts of the binder and dispersant remain unchanged.

[0229] Example 5-1

[0230] The preparation method of the secondary battery is similar to that of Example 1-1, except that the preparation process of the negative electrode plate is different.

[0231] Preparation of the first slurry: 96 wt% of negative electrode active material graphite, 1.8 wt% of binder styrene-butadiene rubber (SBR), and 1.2 wt% of dispersant sodium carboxymethyl cellulose (CMC) were thoroughly stirred and mixed in an appropriate amount of solvent deionized water, and then 1 wt% of amorphous hollow carbon spheres (the same as in Example 1-1) were added to form a first slurry.

[0232] Preparation of the second slurry: 96 wt% of negative electrode active material graphite, 1.8 wt% of binder styrene-butadiene rubber (SBR), and 1.2 wt% of dispersant sodium carboxymethyl cellulose (CMC) were thoroughly stirred and mixed in an appropriate amount of solvent deionized water, and then 1 wt% of amorphous hollow carbon spheres (the same as in Example 1-1) were added to form a second slurry.

[0233] Preparation of the third slurry: 95.4wt% of negative electrode active material graphite, 1.8wt% of binder styrene-butadiene rubber (SBR), and 1.2wt% of dispersant sodium carboxymethyl cellulose (CMC) were thoroughly stirred and mixed in an appropriate amount of solvent deionized water, and then 1.6wt% of amorphous hollow carbon spheres (the same as in Example 1-1) were added to form a third slurry.

[0234] As shown in Figure 1, the first, second, and third slurries are applied simultaneously to the first, second, and third regions of the negative electrode current collector copper foil. After drying and cold pressing, the negative electrode sheet is obtained. The first slurry forms the first portion of the negative electrode active material layer after drying, the second slurry forms the second portion of the negative electrode active material layer after drying, and the third slurry forms the third portion of the negative electrode active material layer after drying.

[0235] Examples 5-2 to 5-6

[0236] The preparation method of the secondary battery is similar to that of Example 5-1, except that the preparation parameters of the negative electrode sheet are different. The specific parameters are detailed in Table 5, and in the preparation of the negative electrode sheet, the addition amounts of the binder and dispersant remain unchanged.

[0237] Test section

[0238] (1) The thickness d of the additive shell and the volume V of the additive cavity h , the volume of the additive V w test

[0239] A circular sample with a diameter of 0.5 cm was cut from the negative electrode sheet prepared above, and a TEM image of the cross section was obtained using a transmission electron microscope (TEM). The thickness of the shell wall of the additive and the volume particle size of the additive in the region were statistically analyzed to obtain the cumulative distribution curves of the thickness of the shell wall of the additive and the volume particle size of the additive, respectively. The thickness corresponding to the 50% percentage on the cumulative distribution curve was taken as the thickness d of the shell wall of the additive, and the volume particle size corresponding to the 50% percentage on the cumulative distribution curve was taken as the volume particle size Dv50 of the additive. According to the calculation formula of an ideal sphere, and with the volume particle size Dv50 obtained above as the diameter, the volume V of the additive was calculated. w , V w =(4 / 3)×π×(Dv50 / 2) 3 , the volume of the additive cavity V h =(4 / 3)×π×(Dv50 / 2-d) 3 The testing instrument may be a Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.

[0240] (2) Porosity test of negative electrode

[0241] Wipe off the negative electrode active material layer on one side of the negative electrode current collector, then punch the negative electrode sheet into small disc samples of a certain area and calculate the apparent volume V1 of the negative electrode sheet. Referring to GB / T24586-2009, use an inert gas (such as helium or nitrogen) as the medium, adopt the gas displacement method, and use a true density tester to measure the true volume V2 of the negative electrode sheet. The porosity of the negative electrode sheet = (V1-V2) / V1×100%. Take multiple (such as 30) negative electrode sheet samples with good appearance and no powder loss on the edges for testing, and average the results to improve the accuracy of the test results. The test instrument can be a Micromeritics AccuPyc II 1340 true density tester.

[0242] (3) Area test of single-layer negative electrode

[0243] The area of ​​a single-layer negative electrode sheet = the circumference of the winding needle × 0.5 × the width of the negative electrode sheet.

[0244] (4) Initial capacity C0 test of secondary battery

[0245] At 25°C, the secondary battery is charged to 3.65V at a constant current of 1C. After standing for 30 minutes, it is discharged to 2.5V at a constant current of 1C. This is a cycle of charge and discharge. The discharge capacity at this time is recorded, which is the initial capacity C0 of the secondary battery.

[0246] (5) Cycle performance test of secondary batteries

[0247] At 25°C, charge the secondary battery at a constant current of 1C to 3.65V, let it stand for 30 minutes, and then discharge it at a constant current of 1C to 2.5V. This is a cyclic charge and discharge process. Record the discharge capacity at this time, which is the initial capacity of the secondary battery. Perform a cyclic charge and discharge test on the secondary battery according to the above method, record the discharge capacity after each cycle, until the discharge capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, and record the number of cycles.

[0248] (6) Thickness rebound rate test of negative electrode active material layer

[0249] ε is the thickness rebound rate of the third portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, ε=(H′−H) / H.

[0250] ε1 is the thickness rebound rate of the first portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, ε1 = (H1′-H1) / H1,

[0251] ε2 is the thickness rebound rate of the second portion of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, ε2=(H2′-H2) / H2.

[0252] H', H1' and H2' are the thicknesses of the third part, first part and second part of the negative electrode active material layer tested when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, respectively. The thicknesses can be obtained by testing according to the following method: at 25°C, the secondary battery is charged to 3.65V at a constant current of 1C, and after standing for 30 minutes, it is discharged to 2.5V at a constant current of 1C. This is a cyclic charge and discharge process, and the discharge capacity at this time is recorded, which is the initial capacity of the secondary battery; the secondary battery is subjected to a cyclic charge and discharge test according to the above method, and the discharge capacity after each cycle is recorded until the discharge capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery; the negative electrode sheet is disassembled from the secondary battery, and the negative electrode sheet is immersed in an organic solvent (for example, dimethyl carbonate) for a period of time (for example, more than 72 hours), and then the negative electrode sheet is taken out and dried at a certain temperature and time (for example, vacuum oven 80°C, drying for more than 6 hours), and then the thicknesses of the third part, first part and second part of the negative electrode active material layer are tested respectively.

[0253] H, H1 and H2 are the initial thicknesses of the third part, the first part and the second part of the negative electrode active material layer, respectively. In each embodiment and comparative example of the present application, H, H1 and H2 all adopt the thickness of the negative electrode active material layer after cold pressing, i.e., 70 μm.

[0254] (7) Expansion force test of secondary batteries

[0255] At 25°C, the secondary battery was charged at a constant current of 1C to 3.65V. After standing for 30 minutes, it was discharged at a constant current of 1C to 2.5V. This constituted one charge-discharge cycle, and the discharge capacity at this point was recorded as the initial capacity of the secondary battery. The secondary battery was then subjected to a cyclic charge-discharge test according to the above method, with the discharge capacity recorded after each cycle until the discharge capacity of the secondary battery decayed to 80% of its initial capacity. During the cycling process, as shown in Figure 8, secondary battery 5 was placed between steel plates 301 and 302, and force sensor 201 was placed between steel plates 302 and 303. The expansion force was monitored when the discharge capacity of the secondary battery decayed to 80% of its initial capacity. The results are shown in Tables 1 to 6.

[0256] From the test results of Table 1 to Table 6, it can be seen that when the negative electrode is added with the material satisfying 20nm≤d≤300nm and 40%≤V h / V wWhen the additive content is ≤90%, the expansion force of the secondary battery can be effectively reduced, thereby improving the safety performance of the secondary battery, while maintaining a low additive dosage and without affecting the energy density. Optionally, the additive dosage is 0.01wt%-3wt%, more preferably 0.1wt%-2wt%. As the additive dosage increases, the effect of further reducing the expansion force of the secondary battery decreases, and the energy density of the secondary battery is also negatively affected.

[0257] It can be seen from the test results in Tables 1 to 6 that when the secondary battery satisfies 100≤K≤30000, optionally, 120≤K≤8000, the secondary battery may have a smaller expansion force.

[0258] Based on the test results of Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-2, Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-2, it can be seen that when the thickness d of the shell wall of the additive is less than 20 nm and the volume proportion of the cavity of the additive is V h / V w Greater than 90%, the thickness d of the additive shell is greater than 300nm, and the volume proportion of the additive cavity is V h / V w When the content is less than 40%, the expansion force of the secondary battery cannot be effectively reduced.

[0259] It can be seen from the test results of Examples 2-1 to 2-4 and Examples 3-1 to 3-5 that when the amount of additives is the same, when the volume of the cavity of the additive accounts for V h / V w Further satisfying 60%≤V h / V w ≤90%, optionally, 70%≤V h / V w When the content of the secondary battery is less than or equal to 89%, the secondary battery may have smaller expansion force.

[0260] It can be seen from the test results of Example 2-1 and Examples 4-1 to 4-4 that the volume of the cavity of the additive accounts for V h / V w Under the conditions that the thickness is close to the shell wall and the amount of additive is the same, when the volume particle size of the additive is greater than 0.8μm, can be selected as 0.85μm-5μm, and can be selected as 1μm-2.5μm, it is more conducive to reducing the expansion force of the secondary battery and also conducive to improving the cycle performance of the secondary battery.

[0261] Based on the test results of Example 1-3 and Example 5-5, Example 1-4 and Example 5-4, Example 1-6 and Example 5-1, Example 1-9 and Example 5-2, it can be seen that by further adjusting the distribution of additives in the width direction of the negative electrode active material layer, using a high content of additives in the third part and a low content of additives in the first part and the second part, it is possible to further reduce the actual amount of additives in the negative electrode sheet when the expansion force of the secondary battery is equivalent, thereby further improving the energy density of the secondary battery.

[0262] Based on the test results of Example 5-2 and Example 5-3, it can be seen that further increasing the amount of additives in the third part of the negative electrode active material layer on the basis of Example 5-2 will not further significantly increase the improvement effect on the expansion force of the secondary battery. Therefore, this application can also guide the amount of additives in the negative electrode sheet, thereby further improving the energy density of the secondary battery.

[0263] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

[0264]

[0265]

[0266]

Claims

1. A negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein: The negative electrode active material layer includes a negative electrode active material and an additive. The additive includes a shell wall and a cavity located inside the shell wall. The thickness of the shell wall is denoted as d, and the volume of the cavity is denoted as V. h , the volume of the additive is recorded as V w , and the additive satisfies 20nm≤d≤300nm and 40%≤V h / V w ≤90%.

2. The negative electrode sheet according to claim 1, wherein, 25 nm ≤ d ≤ 200 nm, optionally, 40 nm ≤ d ≤ 120 nm; and / or, 60%≤V h / V w ≤90%, optionally, 70%≤V h / V w ≤89%.

3. The negative electrode sheet according to claim 1 or 2, wherein: The thickness d of the shell wall of the additive, the volume V of the cavity of the additive h and the volume V of the additive w The test was performed as follows: a circular sample with a diameter of 0.5 cm was cut out from the negative electrode sheet, a TEM image of the cross section was obtained by transmission electron microscopy, the thickness of the shell wall of the additive and the volume particle size of the additive in the region were counted, and the cumulative distribution curves of the thickness of the shell wall of the additive and the volume particle size of the additive were obtained respectively. The thickness corresponding to the 50% percentage on the cumulative distribution curve was taken as the thickness d of the shell wall of the additive, and the volume particle size corresponding to the 50% percentage on the cumulative distribution curve was taken as the volume particle size Dv50 of the additive. According to the calculation formula of an ideal sphere, and with the volume particle size Dv50 obtained above as the diameter, the volume V of the additive was calculated. w , V w =(4 / 3)×π×(Dv50 / 2) 3 , the volume V of the cavity of the additive h =(4 / 3)×π×(Dv50 / 2-d) 3 .

4. The negative electrode sheet according to any one of claims 1-3, the additive includes one or more selected from hollow spheres and hollow polyhedrons, and may optionally include hollow spheres; and / or, the volume particle size Dv50 of the additive is 0.85 μm - 5 μm, and may optionally be 1 μm - 2.5 μm; and / or, the volume particle size of the additive satisfies 0.5 ≤ (Dv90 - Dv10) / Dv50 ≤ 8, and optionally, 2 ≤ (Dv90 - Dv10) / Dv50 ≤ 5.

5. The negative electrode sheet according to any one of claims 1 to 4, wherein: The additive includes hollow carbon spheres, and may optionally include one or more selected from amorphous hollow carbon spheres, graphitized hollow carbon spheres, and hollow graphene spheres.

6. The negative electrode sheet according to any one of claims 1 to 5, wherein: Based on the total weight of the negative electrode active material layer, the weight percentage content of the additive is 0.01 wt% - 3 wt%, and may optionally be 0.1 wt% - 2 wt%.

7. The negative electrode sheet according to any one of claims 1 to 6, wherein: Along the width direction of the negative electrode active material layer, the negative electrode active material layer includes a first part and a second part located on the edge side and a third part located between the first part and the second part. Taking the total width of the negative electrode active material layer as W, the width of the first part is 1 / 5W, the width of the second part is 1 / 5W, the width of the third part is 3 / 5W, the weight percentage content of the additive in the first part is w1, the weight percentage content of the additive in the second part is w2, the weight percentage content of the additive in the third part is w3, and 0 ≤ w1 / w3 < 1, 0 ≤ w2 / w3 < 1.

8. The negative electrode sheet according to claim 7, wherein, 0 < w1 / w3 ≤ 0.7, and optionally, 0 < w1 / w3 ≤ 0.5; and / or, 0 < w2 / w3 ≤ 0.7, and optionally, 0 < w2 / w3 ≤ 0.

5.

9. The negative electrode sheet according to claim 7 or 8, wherein, 0 wt% ≤ w1 ≤ 2 wt%, and optionally, 0 wt% < w1 ≤ 1 wt%; and / or, 0 wt% ≤ w2 ≤ 2 wt%, and optionally, 0 wt% < w2 ≤ 1 wt%; and / or, 0.01 wt% ≤ w3 ≤ 5 wt%, and optionally, 0.01 wt% ≤ w3 ≤ 2 wt%.

10. The negative electrode sheet according to any one of claims 7 to 9, wherein: w1 = w2.

11. The negative electrode sheet according to any one of claims 1 to 10, wherein: Based on the total weight of the negative electrode active material layer, the weight percentage content of the negative electrode active material is 95 wt% - 99 wt%.

12. The negative electrode sheet according to any one of claims 1 to 11, wherein: The negative electrode active material layer further includes a negative electrode binder and / or a negative electrode dispersant, optionally, based on the total weight of the negative electrode active material layer, the weight percentage content of the negative electrode binder is 1 wt% - 2.5 wt%; optionally, based on the total weight of the negative electrode active material layer, the weight percentage content of the negative electrode dispersant is 0.5 wt% - 1.5 wt%.

13. The negative electrode sheet according to any one of claims 1 to 12, wherein: The negative electrode active material layer further includes a negative electrode conductive agent, and optionally, based on the total weight of the negative electrode active material layer, the weight percentage content of the negative electrode conductive agent is 0 wt% - 1.5 wt%.

14. A method for preparing a negative electrode sheet, comprising the steps of: providing a negative electrode slurry comprising a negative electrode active material and an additive; coating the negative electrode slurry on a negative electrode current collector, drying, and cold pressing to obtain a negative electrode sheet, wherein: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and an additive. The additive includes a shell wall and a cavity located inside the shell wall. The thickness of the shell wall is denoted as d, and the volume of the cavity is denoted as V. h , the volume of the additive is recorded as V w , and the additive satisfies 20nm≤d≤300nm and 40%≤V h / V w ≤90%.

15. The preparation method according to claim 14, wherein Along the width direction of the negative electrode current collector, the negative electrode current collector includes a first region and a second region located on the edge sides, and a third region located between the first region and the second region. Taking the total width of the coating region of the negative electrode current collector as W, the width of the first region is 1 / 5W, the width of the second region is 1 / 5W, and the width of the third region is 3 / 5W. In the method for preparing the negative electrode sheet, the negative electrode paste is formulated to include a first paste, a second paste, and a third paste, and then the first paste, the second paste, and the third paste are respectively coated on the first region, the second region, and the third region of the negative electrode current collector, and after drying, a first part, a second part, and a third part of the negative electrode active material layer are respectively formed. Among them, the weight percentage content of the additive in the first part is w1, the weight percentage content of the additive in the second part is w2, and the weight percentage content of the additive in the third part is w3, and 0 ≤ w1 / w3 < 1, 0 ≤ w2 / w3 < 1. Optionally, the first paste, the second paste, and the third paste are coated by a one-time simultaneous coating process or a multiple-step coating process.

16. A secondary battery, including the negative electrode sheet according to any one of claims 1-13, or a negative electrode sheet prepared by the preparation method according to any one of claims 14-15.

17. The secondary battery according to claim 16, wherein The secondary battery satisfies 100 ≤ K ≤ 30000, optionally, 120 ≤ K ≤ 8000. λ is the porosity of the negative electrode sheet. ε is the thickness rebound rate of the third part of the negative electrode active material layer when the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery. C0 is the initial capacity of the secondary battery, with the unit of mAh. d is the thickness of the shell wall of the additive, with the unit of nm. V h is the volume of the cavity of the additive, in nm 3 ; S is the area of ​​the single-layer negative electrode sheet, in mm 2 ; H is the initial thickness of the third part of the negative electrode active material layer, with the unit of μm.

18. The secondary battery according to claim 17, wherein The secondary battery satisfies at least one of the following: (1) 20% ≤ λ ≤ 50%, optionally, 23% ≤ λ ≤ 35%. (2) 20% ≤ ε ≤ 40%, optionally, 25% ≤ ε ≤ 35%. (3) 20 nm ≤ d ≤ 300 nm, optionally, 40 nm ≤ d ≤ 120 nm. (4)1×10 7 nm 3 ≤V h ≤1×10 12 nm 3 , optionally, 2.5×10 8 nm 3 ≤V h ≤1×10 10 nm 3 ; (5)1×10 2 mm 2 ≤S≤1×10 8 mm 2 , optionally, 1×10 3 mm 2 ≤S≤1×10 6 mm 2 ; (6) 10 μm ≤ H ≤ 250 μm, optionally, 40 μm ≤ H ≤ 120 μm.

19. The secondary battery according to claim 17 or 18, wherein When the capacity of the secondary battery decays to 80% of the initial capacity of the secondary battery, the thickness rebound rate of the first part of the negative electrode active material layer is denoted as ε1, the initial thickness of the first part of the negative electrode active material layer is denoted as H1, with the unit of μm, the thickness rebound rate of the second part of the negative electrode active material layer is denoted as ε2, the initial thickness of the second part of the negative electrode active material layer is denoted as H2, with the unit of μm, and the secondary battery satisfies 0 < K1 / K ≤ 1, 0 < K2 / K ≤ 1.

20. The secondary battery according to claim 19, wherein 0 < K1 / K ≤ 0.95; and / or 0 < K2 / K ≤ 0.

95.

21. The secondary battery according to claim 19 or 20, wherein 100≤K1≤30000, optionally, 120≤K1≤8000; and / or, 100≤K2≤30000, optionally, 120≤K2≤8000.

22. The secondary battery according to any one of claims 19 to 21, wherein: 15%≤ε1≤35%, optionally, 25%≤ε1≤31%; and / or, 15%≤ε2≤35%, optionally, 25%≤ε2≤31%; and / or, 10 μm ≤ H1 ≤ 250 μm, optionally, 40 μm ≤ H1 ≤ 120 μm; and / or, 10μm≤H2≤250μm, optionally, 40μm≤H2≤120μm.

23. An electrical device comprising the secondary battery according to any one of claims 16 to 22.